Pemetaan Kualifikasi Agregat Halus Sebagai Material Konstruksi di Provinsi Sulawesi Utara - Sengkey, Sandri Linna; Slat, Ever N.; Nicolaas, Seska; Mantiri, Nixon Servius; Slat, Ventje Berty (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
The quality of the concrete mix is influenced by many factors, one of which is the constituent material. Sand, as one of the concrete forming materials, also contributes to improving the quality and performance of concrete. This study aims to determine the physical characteristics of fine aggregates in North Sulawesi Province and their suitability as concrete materials and their implementation in concrete mix design. The research method in the form of laboratory research includes testing of specific gravity and absorption, sieve analysis, organic material content, silt content and unit weight of sand from 20 quarry sites in North Sulawesi Province. The results of the study showed that 15 sand quarries met the specification standards as concrete materials, while 5 quarries did not meet the specification standards, especially in terms of specific gravity and absorption properties, and fineness modulus, which exceeded the maximum specification limit. The sand grading in North Sulawesi is mostly in the rather coarse sand criteria and is in zone 2. The results of this sand qualification are expected to be useful in concrete mix design.